Cultural aspects of the formation of administrative law principles: from antiquity to modern times - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In modern science of administrative law it’s common to distinguish two models: a closed one corresponding to the authoritarian model of governance and an open model that reflects the nature of European administrative law in the developed democracies. Accordingly the systems of governing the states and societies are constructed: at one pole – the company that can be called collectivist (closed), on the other – individualistic society (open). In the article a direct link between these types of companies and types prevailing in their societies’ cultures is emphasized – both in space and on the grounds, and in time. According to Dutch researcher G. Hofstede, all cultures are classified as individualistic or collectivist. In individualistic societies, people are guided by their own interests and goals. Among the main values of such companies dominate respect for human rights and the high value of individual human life. In contrast to such societies collectivist ones provide a full «immersion» of the birth of the benefit of the group (family, clan) in exchange for security (although often a relative). Own interests almost are not counted if are inconsistent with or not supported by the group. According to the classification of G. Hofstede, there are 8 types of crops, including 5 types of crops are of low or moderate hierarchy and high level of individualism and personal freedoms, 2 types – with high levels of the hierarchy, low individualism, 1 type – with a moderate level of hierarchy and individualism. It was established that the above list of top 5 types correspond to representations of those countries where the open model of European administrative law, while others – closed and partially closed model of administration. Similar correlations can be traced in time (in a historical context). For example the ancient individualistic society can serve as Ancient Greece, above all, the Athenian democracy. Hellenic tradition presents us with the phenomenon of the free citizen, who is an independent private owner, and with the same economically independent owners forming civil society, subordinating state institutions. Such type of society corresponding to the cultural traditions of the Greek civilization, which is of particular importance, is the individual, personal creativity. Collectivism is not omnipotent; it co-existed in a dialectical confrontation with individualism, with a high value card (there is no doubt that this value is in Greece and in the ancient world as a whole was significantly higher than in the Ancient East). Correlation is also evident cultural, administrative and legal traditions of the Middle Ages, including the medieval town (in connection with the Magdeburg right), collectivist (closed) model of culture and management in Russia and effective denazification of Germany, a factor which acts, in particular the rejection of the Nazi German cultural tradition.